Malaria transmission in the vicinity of impounded water: evidence from the Koka Reservoir, Ethiopia - Kibret, S.; McCartney, Matthew P.; Lautze, Jonathan F.; Jayasinghe, G. (International Water Management Institute, 2009)
The construction of dams in Africa is often associated with adverse malaria impacts in surrounding communities. However, the degree and nature of these impacts are rarely quantified and the feasibility of manipulating reservoir water levels to control mosquito breeding has not been previously investigated in Africa. This report describes entomological and epidemiological studies conducted around the Koka Dam and Reservoir in Ethiopia. The research findings confirm the role of the reservoir in increasing malaria transmission and provide evidence that there is potential to use dam operation in integrated malaria control strategies.